Contemporary Fiqh Learning Module at Mosques in Malaysia - Azhar, Alias (EDUCARE, 2013)
ABSTRACT: This paper focuses on the module development model for âtafaqquhâ at the mosque. The âtafaqquhâ programme has been systematically conducted jointly by Malaysia Islamic Development Department, the State Islamic Affairs Department and mosquesâ management committees. The programme has been made successful and effective by the contribution and cooperation of âtakmirâ teachers whoÂ have beenÂ appointed and trained intensively. These âtakmirâ teachers play very significant roles in the realisation of the aspiration and the scheme in developing knowledgeable society through the involvement of the mosque. To get the holistic view of the theme and subject of the study, focus is made on several key elements: the history of the development of Islamic studies module in the societies of the Muslim civilization; Islamic education theory which correlates to the National Philosophy of Islamic Education; âfiqhâ learning method from the current methodology and pedagogy; and finally the presentation of the current âtafaqquhâ module of alternative Islam in Malaysia. The learning of âfiqhâ must be viewed from a broad context and it should be able to have an influence on the life of human beings from all living aspects.The philosophy of Islamic education, which is based on Al-Qurâan and Al-Sunnah, should be able to be implemented realistically. The modification and upgrade ofÂ the âfiqhâ learning syllabus in mosques require a drastic approach, besides practical module construction. Through these, it is hoped that the learning of âfiqhâ through the âtafaqquhâ program in mosques will progress on par with modernisation and current ââurfâ awareness in the society.KEY WORDS: âTafaqquhâ programme, âfiqhâ learning, Islamic education, national philosophy, Muslim society, and mosques in Malaysia.About the Author: Dr. Alias Azhar is a Senior Lecturer at the School of Law, College of Law, Government, and International Studies UUM (University of Utara Malaysia), 06010 Sintok, Kedah Darul Aman, Malaysia. For academic purposes, the author can be contacted via: Phone: +6012-5898510 or +604-9284953. Fax: +604-9286563/6565. E-mail: az.alias@uum.edu.myHow to cite this article? Azhar, Alias. (2013). âContemporary Fiqh Learning Module at Mosques in Malaysiaâ in EDUCARE: International Journal for Educational Studies, Vol.6(1) August, pp.69-80. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 19, 2013); Revised (July 23, 2013); and Published (August 17, 2013).Â Â